2020
DOI: 10.3390/agronomy10111654
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Light-Emitting Diode Treatment on Defence System and Changes in Mesocarp Metabolites of Avocados Cultivars (Hass and Fuerte) during Simulated Market Shelf Conditions

Abstract: The ability of light-emitting diode (LED) light treatment to reduce the anthracnose decay via its eliciting effects and thus induce resistance in the avocado (Persea americana), was investigated in this study to replace the current postharvest fungicide treatment. In experiment 1, the effect of blue or red LED lights (6 h per day) on the incidence of anthracnose in artificially inoculated (Colletotrichum gloesposorioides) and naturally infected avocados (cv. Fuerte and Hass) at 12–14 °C (simulated market shelf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In this study, mean temperature of the quarter showed little significance in morphological traits, perhaps due to all sampling sites belonging to the subtropical monsoon climate and no strict temperature limit for persimmon survival. Consistent with previous studies of many fruit trees, which revealed that light [59][60][61] and water supply [62][63][64][65][66] played an important cue in both leaf and fruit development, and precipitation and solar radiation were the main climate factors affecting the morphological traits of persimmon in Zhejiang Province. There were also longitudinal differences in morphological trait diversity.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, mean temperature of the quarter showed little significance in morphological traits, perhaps due to all sampling sites belonging to the subtropical monsoon climate and no strict temperature limit for persimmon survival. Consistent with previous studies of many fruit trees, which revealed that light [59][60][61] and water supply [62][63][64][65][66] played an important cue in both leaf and fruit development, and precipitation and solar radiation were the main climate factors affecting the morphological traits of persimmon in Zhejiang Province. There were also longitudinal differences in morphological trait diversity.…”
Section: Discussionsupporting
confidence: 90%
“…The LED blue light treatments could have induced the activation of the shikimate pathway to increase the concentration of the precursors for the production of different phenolic compounds via the phenylpropanoid pathway ( 41 ). Red LED light increased the biosynthesis of flavonoid (epicatechin) in avocados by inducing the upregulation of phenylalanine ammonia-lyase gene expression ( 11 ). However, Liu et al ( 42 ) showed that compared to red light, the blue light-induced a higher flavonoid accumulation in Cyclocarya paliurus leaves, especially key health-promoting flavonoids such as kaempferol, and quercetin.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in yellow and green fresh-cut sweet peppers, red LED light and in red fresh-cut sweet pepper, blue LED light enabled the accumulation of phenolic compounds by inducing the activity of phenylalanine ammonia-lyase (PAL) ( 10 ). In avocados, red LED lights improved the accumulation of epicatechin content in the fruit by upregulating the PAL genes ( 11 ). LED red light treatment improved the lycopene and β-carotene, total phenols, and flavonoids in tomatoes during post-harvest storage ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated that phytochromes (PhyA to PhyE) absorb red light and are essential for synthesising phenolic compounds and antioxidants (Li & Kubota, 2009). Maroga et al (2019) and Mpai & Sivakumar (2020) suggest that red LED light activates phenylalanine ammonia lyase (PAL), which produces secondary metabolites (phenols). Reported that light enhances the production of phenolic content by creating malonyl CoA and coumaroyl CoA.…”
Section: Total Phenol Content (Tpc)mentioning
confidence: 99%